ChemInform Abstract: Tailoring Two Polymorphs of LiFePO4 by Efficient Microwave‐Assisted Synthesis: A Combined Experimental and Theoretical Study. Issue 46 (24th October 2013) - Zeng, Guobo; Caputo, Riccarda; Carriazo, Daniel; Luo, Li; Niederberger, Markus
Abstract Both α‐ and β‐LiFePO4 are synthesized from solutions of LiCl, Fe(OAc)2, and H3PO4 in a mixture of benzyl alcohol and 2‐pyrrolidinone in the ratios 4:1 and 1:1, respectively (microwave irradiation, 195 °C, 3 min).